2015
DOI: 10.1038/srep08364
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 forms mechanosensitive ion channels in the human MCF-7 breast cancer cell line

Abstract: Mechanical interaction between cells – specifically distortion of tensional homeostasis-emerged as an important aspect of breast cancer genesis and progression. We investigated the biophysical characteristics of mechanosensitive ion channels (MSCs) in the malignant MCF-7 breast cancer cell line. MSCs turned out to be the most abundant ion channel species and could be activated by negative pressure at the outer side of the cell membrane in a saturable manner. Assessing single channel conductance (GΛ) for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 49 publications
2
128
1
1
Order By: Relevance
“…The mRNA level of PIEZO1 was shown relatively low in a benign breast epithelial cell line, but highly expressed in the malign MCF‐7 cells and primary tumors. Increase of PIEZO1 correlated with poor overall survival in patients with breast cancer . Besides, PIEZO1 was among the highest expressed genes in thyroid cancers following Iodine‐131 exposure .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mRNA level of PIEZO1 was shown relatively low in a benign breast epithelial cell line, but highly expressed in the malign MCF‐7 cells and primary tumors. Increase of PIEZO1 correlated with poor overall survival in patients with breast cancer . Besides, PIEZO1 was among the highest expressed genes in thyroid cancers following Iodine‐131 exposure .…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, recent studies addressed that when it comes to epithelial cell crowding and cytoskeletal contractions, PIEZO1 could be activated to maintain cell homeostasis of epithelial monolayers . Concerning the distinct role of PIEZO1 in epithelial cells, the functional role PIEZO1 have been investigated in epithelia derived cancers . By performing knockdown experiments, lung cancer cells initiated an undirected migration mode and acquired a more aggressive phenotype to increase cell motility .…”
Section: Introductionmentioning
confidence: 99%
“…To test whether the Piezo1 channel plays a role in regulating hDP‐MSC migration, as recently reported in endothelial cell and various cancer cells, we used the wound healing assay to examine the effect of Yoda1 on cell migration (Figure ). Inclusion of 0.1‐1 μM Yoda1 in the culture medium resulted in a concentration‐dependent increase in cell migration, with 0.3 and 1 μM Yoda1 significantly accelerating cell migration at 24, 48, and 72 hours, and such stimulation was observed in hDP‐MSCs from all four donors, with some variations among the different donors (Figure A‐F).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies have reported that mechanical or chemical activation of the Piezo1 channel induces ATP release from endothelial cells, urothelial cells, and red blood cells . There is also compelling evidence to support a critical role for the Piezo1 channel in regulating cell migration in endothelial cells, breast cancer cells, gastric cancer cells, and small lung cancer cells . Recent studies have also shown the expression of the Piezo1 channel in human bone marrow‐derived MSCs (BM‐MSCs) and rat dental pulp‐derived stem cells (DP‐MSCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Highly metastatic breast cancer cells exhibit high Piezo1 expression, which has been correlated with worse outcomes in one patient population [63]. Metastatic breast cancer cells, invasive melanoma cells and gastric cancer cells exhibited reduced migration when Piezol was knocked down or pharmacologically inhibited [29,63,64]. In these cell types, higher Piezo1 activity has been proposed to underlie greater migration associated with the metastatic state.…”
Section: Effect Of Piezo1 Activity On the Cytoskeletonmentioning
confidence: 99%